2022
DOI: 10.34190/ecgbl.16.1.603
|View full text |Cite
|
Sign up to set email alerts
|

Refurbishing the Educational Escape Room for Programming: Lowering the Threshold and Raising the Ceiling

Abstract: Programming education at university level has often been identified as problematic learning. At the same time, prognosis for future labour market is increased need for professionals with programming and related skills. To meet demands of future society, K-12 schools around the world have integrated programming in the curriculum. However, research show challenges for integrating programming in K-12 education. Challenges include students’ and teachers’ struggle with learning and teaching programming, lack of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…1), and the focus is on the basics of programming with the programming language Python, combined with fundamental ideas from Computational Thinking (CT), such as CT concepts, practices, and perspectives [47]. The syllabus framework, created and distributed by the Swedish national Agency for Education, for elementary school teachers' professional development in programming was used as a guideline for constructing the content of the game (or the challenges in each escape room) [48]. The concepts that constitute the challenges of the game, and were chosen from the syllabus framework, are variables, sequences, conditions, iterations, and functions.…”
Section: Prototype Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1), and the focus is on the basics of programming with the programming language Python, combined with fundamental ideas from Computational Thinking (CT), such as CT concepts, practices, and perspectives [47]. The syllabus framework, created and distributed by the Swedish national Agency for Education, for elementary school teachers' professional development in programming was used as a guideline for constructing the content of the game (or the challenges in each escape room) [48]. The concepts that constitute the challenges of the game, and were chosen from the syllabus framework, are variables, sequences, conditions, iterations, and functions.…”
Section: Prototype Developmentmentioning
confidence: 99%
“…Secondly, it is essential for game design to investigate the specific design factors for an educational game on learning to program. For a merge of these two aspects authors have combined the data sets from two earlier studies [20][21]. Carried out with a Design science approach, the aim of this study is to collect requirements for the development of a conceptual model.…”
Section: Introductionmentioning
confidence: 99%
“…Game-based learning (GBL) has emerged as a promising approach that effectively motivates students while simultaneously maintaining focus on learning (Klopfer, Osterweil & Salen, 2009;Humble, Mozelius & Sällvin, 2021;Humble, N., & Mozelius, P., 2022). Previous research has also shown promising results regarding students' engagement and attitudes towards computer programming when using GBL (Papadakis & Kalogiannakis, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to a report, 6 out of 10 Swedish internet users play games on either mobile devices, computers, or gaming consoles (Internetstiftelsen [The Swedish Internet Foundation], 2022). Games are also widely used for learning, both formal (Pan, Ke & Xu, 2022;, informal (Koutromanos & Avraamidou, 2014;Humble, Mozelius & Sällvin, 2021), and non-formal (Pienimäki, Kinnula & Iivari, 2021).…”
Section: Introductionmentioning
confidence: 99%